Anatomical study of ultrasound vs landmark guidance for needle placement in the obliquus capitis inferior - Jacobo Rodríguez-Sanz; César Fernández-de-las-Peñas; Sergio Borrella-Andrés; Carlos López-de-Celis; José L. Arias-Buría; Albert Pérez-Bellmunt; Isabel Albarova-Corral; Miguel Malo-Urriés (Scientific Reports)
Abstract Needling of obliquus capitis inferior (OCI) muscle could be an important intervention for individuals with upper cervical pain; however, precision is important due to its sensitive location. The aim was to assess the accuracy, safety and performance of needling OCI using palpation versus ultrasound-guidance in a cadaveric model. A cross-sectional anatomical study was conducted. Five therapists each performed a series of 20 needle insertion tasks (n = 100) on 10 anatomical samples. Distance from the needle tip to the target, if the OCI muscle belly was reached (accuracy), surrounding sensitive structures targeted (safety), time needed, number of needles passes, and the length of the needle remaining outside the skin were assessed. The ultrasound-guided procedure was associated with significantly greater accuracy and safety (p < 0.001). The ultrasound-guided procedure achieved 100% accuracy of reaching the OCI compared to 40% with the palpation-guided procedure, with a shorter distance from the needle tip to the target. In the palpation-guided procedure, potentially sensitive structures were pierced in 38% of cases compared to only 4% with the ultrasound-guided approach. However, the palpation-guided procedure required less time and fewer passes. Our findings suggest that ultrasound-guided procedure showed greater accuracy and safety than palpation-guided procedures for properly targeted the OCI muscle belly.